2009
DOI: 10.4049/jimmunol.0802270
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Eosinophils and Their Role in Immunopathologic Responses to Formalin-Inactivated Pneumonia Virus of Mice

Abstract: Enhanced disease is the term used to describe the aberrant Th2-skewed responses to naturally acquired human respiratory syncytial virus (hRSV) infection observed in individuals vaccinated with formalin-inactivated viral Ags. Here we explore this paradigm with pneumonia virus of mice (PVM), a pathogen that faithfully reproduces features of severe hRSV infection in a rodent host. We demonstrate that PVM infection in mice vaccinated with formalin-inactivated Ags from PVM-infected cells (PVM Ags) yields Th2-skewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…Expression of the PVM SH gene as an indicator of virus burden (29) was greatest at day 6 after inoculation (Fig. 1A) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the PVM SH gene as an indicator of virus burden (29) was greatest at day 6 after inoculation (Fig. 1A) .…”
Section: Resultsmentioning
confidence: 99%
“…PCR reactions to quantitatively detect cytokine and chemokine RNAs used probe sets from Applied Biosystems and the 7900HT Sequence Detection System. Relative levels of PVM SH gene expression (29) were determined by quantitative RT-PCR, with normalization to Rpl7 expression.…”
Section: Methodsmentioning
confidence: 99%
“…Enhanced disease in FI-PVM-vaccinated mice is associated with a Th2-biased response, production of IL-4, IL-5, IL-13, and pulmonary eosinophilia [159]. In contrast, neutrophils predominate in BAL from mice vaccinated with FI-uninfected cell antigen, and Th2 cytokine levels are low.…”
Section: Non-human Pneumovirus Animal Modelsmentioning
confidence: 94%
“…Eosinophils themselves, depending on factors that we do not yet understand, have antiviral properties in vitro [23][24][25] and can clear virus from infected lung tissue in vivo, 26,27 although not in all circumstances. 56 At the same time, respiratory virus infection is not only a disease of virus replication, because we and others have shown that inflammatory mediators produced locally have a profound effect on the clinical course. 22,57,58 Thus, although eosinophils as targets of virus infection may be releasing a limited number of infectious virions, this might be outweighed by the release of important immunomodulatory cytokines.…”
Section: Discussionmentioning
confidence: 99%